2016
DOI: 10.3762/bjoc.12.251
|View full text |Cite
|
Sign up to set email alerts
|

Thiazol-4-one derivatives from the reaction of monosubstituted thioureas with maleimides: structures and factors determining the selectivity and tautomeric equilibrium in solution

Abstract: 2-(Alkyl(aryl)amino)thiazol-4(5H)-ones can regioselectively be prepared from monoalkyl(aryl)thioureas and maleimides. In solution, the former heterocycles exist in a tautomeric equilibrium with 2-(alkyl(aryl)imino)thiazolidin-4-ones and the substituent on the exocyclic nitrogen atom governs the ratio of these tautomers. Isomers with the alkyl group in the endocyclic position can be obtained from N-methyl(ethyl)thioureas. 2D NMR spectroscopy and DFT calculations rationalize experimental results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The synthetic pathway for title compound was carried out as outlined in Scheme 1. The substituted thiazolidinone derivative was obtained by the reaction of 3-(4-chlorophenyl)-5-[4-(propan-2-yl)phenyl]-4,5-dihydro-1H-pyrazole-1-carbothioamide with N-(4-nitrophenyl)maleimide under a reflux condition in glacial acetic acid [13,14]. The analytical and spectral data confirmed the structure and purity of the newly synthesized title compound (2).…”
Section: Resultsmentioning
confidence: 74%
“…The synthetic pathway for title compound was carried out as outlined in Scheme 1. The substituted thiazolidinone derivative was obtained by the reaction of 3-(4-chlorophenyl)-5-[4-(propan-2-yl)phenyl]-4,5-dihydro-1H-pyrazole-1-carbothioamide with N-(4-nitrophenyl)maleimide under a reflux condition in glacial acetic acid [13,14]. The analytical and spectral data confirmed the structure and purity of the newly synthesized title compound (2).…”
Section: Resultsmentioning
confidence: 74%
“…In the reactions of N-arylmaleimides with thiourea and its derivatives, five-and sixmembered heterocycles are usually formed: thiazoles B [1,7,[13][14][15][16][17][18] and thiazines C [20]. Reactions of N-arylmaleimides with polynucleophilic reagents, such as amidinothiourea and thiosemicarbazones proceed at 1,3-S,N-binucleophilic centers with the formation of the corresponding thiazolines [2,3,21,22].…”
Section: Resultsmentioning
confidence: 99%
“…N-substituted maleimides are promising organic substrates that are used to build a wide range of fused and linearly linked heterocyclic scaffolds with biologically active properties [1][2][3][4][5][6][7][8][9]. The reactive feature of maleic acid imides is their ability to enter into 1,3-dipolar addition reactions [8][9][10][11][12] and into recyclization reactions under the action of binucleophilic reagents-in particular, 1,3-S,N-binucleophiles [1][2][3][4][5][6][7][13][14][15][16][17][18][19][20][21][22][23]. In such reactions, the addition of a more nucleophilic sulfur atom to the activated double bond of N-substituted maleimide usually occurs at the first stage, and the recyclization of the succinimide ring under the action of the nucleophilic nitrogen atom occurs at the second stage [19,21] (Scheme 1, adduct A).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the case of N,N-substituted thioureas, the reaction can proceed via several alternative routes (Scheme 27). Thus, the study of A. S. Pankova [109] showed that the reaction of N-alkylthioureas with maleimides at room temperature in ethanol can lead to the formation of mixture 104 and 105. In addition, the nature of the solvent, substituents, and the steric factor play an important role in the formation of specific regioisomers [110].…”
Section: Reactions With Polynucleophilic Reagents and Involvement In ...mentioning
confidence: 99%